2017
DOI: 10.5376/mmr.2017.07.0003
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid and Proximate Composition of <i>Saccharomyces cerevisiae</i> Biomass Cultivated in Cassava Mill Effluents

Abstract: Cassava mill effluent (CME) is generated during cassava processing into cassava flake or gari. The effluents affects the quality of the receiving environment such soil. It is could affect domestic animals such as goat and sheep when they ingest it, and retard normal growth and productivity of plants in the affected soil. This study evaluated amino acid and proximate composition of Saccharomyces cerevisiae cultivated in cassava mill effluents. S. cerevisiae used in this study was isolated from palm wine based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 18 publications
5
34
0
1
Order By: Relevance
“…Based on Table 2, the amino acids of Saccharomyces cerevisiae biomass from both effluents in comparison to Food and Agricultural Organization/World Health Organization limits for single cell protein meant for animal feed revealed that the values of the essential amino acids including isoleucine, leucine, tryptophan, histidine and combination of phenylalanine, tyrosine etc were superior and/ or comparable to recommended limit for single cell protein. On the other hand the total non-essential amino acids were lower compared to Food and Agricultural Organization/World Health Organization limits 54 (Table 2), a trend that have been previously reported by Izah et al 19 in Saccharomyces cerevisiae biomass culture in cassava mill effluents and Iwuagwu and Ugwuanyi 47 in Saccharomyces species biomass cultured in palm oil mill effluents. The values of essential amino acids suggest that they can be used for animal feed if every other nutrient constituent are adequate.…”
Section: Feed Potentials Of Saccharomyces Cerevisiaesupporting
confidence: 60%
See 1 more Smart Citation
“…Based on Table 2, the amino acids of Saccharomyces cerevisiae biomass from both effluents in comparison to Food and Agricultural Organization/World Health Organization limits for single cell protein meant for animal feed revealed that the values of the essential amino acids including isoleucine, leucine, tryptophan, histidine and combination of phenylalanine, tyrosine etc were superior and/ or comparable to recommended limit for single cell protein. On the other hand the total non-essential amino acids were lower compared to Food and Agricultural Organization/World Health Organization limits 54 (Table 2), a trend that have been previously reported by Izah et al 19 in Saccharomyces cerevisiae biomass culture in cassava mill effluents and Iwuagwu and Ugwuanyi 47 in Saccharomyces species biomass cultured in palm oil mill effluents. The values of essential amino acids suggest that they can be used for animal feed if every other nutrient constituent are adequate.…”
Section: Feed Potentials Of Saccharomyces Cerevisiaesupporting
confidence: 60%
“…Saccharomyces cerevisiae cultured in cassava mill effluents have been reported to contain essential heavy metals, 20 low cyanide and cations, 18 proximate composition and amino acids. 19 Furthermore, proximate composition, amino acids, heavy metals, cations, etc have been reported in brewer's yeast. 51 52 reported that Saccharomyces cerevisiae (BY 4743) could enhance the protein content of potato peels through fermentation.…”
Section: Feed Potentials Of Saccharomyces Cerevisiaementioning
confidence: 99%
“…Cassava is a major source of staple food to several families in tropical Africa Emurotu et al 1 especially in Nigeria that is the largest producing nation in the world Izah et al, [2][3][4][5][6][7][8][9][10] Izah & Ohimain, 11 Ohimain et al 12 Cassava cultivation and processing is carried out predominantly by smallholder in Nigeria. According to Kigigha et al 13 cassava cultivation, processing and marketing of its associated products is a major source of livelihood to several families especially in rural setting in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Several human activities that impact on the soil including municipal solid wastes that are poorly managed in many developing countries [10], food processing effluents such as oil palm processing wastewater [11,12] and cassava mill effluents [1][2][3][13][14][15][16][17][18][19][20][21], wastes emanating from markets [22][23][24], slaughterhouse [25] etc. These wastes stream have the tendency to alter the characteristics of the receiving soil.…”
Section: Introductionmentioning
confidence: 99%
“…Basically Nigeria is the global leading cassava producing countries [14][15][16][17][18][19][20][21][26][27][28][29][30]. The cassava production in Nigeria has exceeded the combined production of second (Thailand) and third (Indonesia) largest cassava production countries in the world.…”
Section: Introductionmentioning
confidence: 99%